2021
DOI: 10.1093/geroni/igab046.3647
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Supervisor Support on the Job Satisfaction of Immigrant and Minority Long-Term Care Workers

Abstract: Caregivers of persons with dementia (PWD) often experience increases in depression, anxiety, and burden as the disease progresses. In fact, as the PWD’s neuropsychiatric symptoms increase and independence in ADLS decrease, caregivers psychological and physical health outcomes worsen. The literature suggests that caregiver interventions that teach specific skills are more beneficial than psychoeducational interventions, particularly regarding the amelioration of the psychological impacts of informal caregiving.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research supports that nursing home aides with low levels of job satisfaction are more likely to turn over within 1 year (Castle et al, 2007; Donoghue, 2010; Jang et al, 2017). The job satisfaction experienced by LTCW is also important for the well-being of not only the workers but also of the residents and families they serve (Hawes, 2020). Research has found that work environments with higher employee satisfaction provide better service to patients (Plaku-Alakbarova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research supports that nursing home aides with low levels of job satisfaction are more likely to turn over within 1 year (Castle et al, 2007; Donoghue, 2010; Jang et al, 2017). The job satisfaction experienced by LTCW is also important for the well-being of not only the workers but also of the residents and families they serve (Hawes, 2020). Research has found that work environments with higher employee satisfaction provide better service to patients (Plaku-Alakbarova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%